Piloting technologies for microplastics removal from urban waters : FanpLESStic-sea project report - Vahvaselkä, Marjatta; Cur, Katarzyna; Drewnowska, Małgorzata; Maunuksela, Jyri; Medyna, Galyna; Winquist, Erika (Natural Resources Institute Finland, 2022)
The FanpLESStic-sea – “Initiatives to remove microplastics before they enter the sea” project funded by the EU Interreg Baltic Sea Region programme aimed at decreasing microplastic (MP) sources and removing MPs before they enter the Baltic Sea. As part of the project, novel and innovative removal technologies and methods for MPs in urban waters were developed and tested in four pilot systems by three project partners: a common reed filter for treatment of urban snow meltwaters and stormwaters by Natural Resources Institute Finland (Luke), an urban snow melting and filtering unit by Clewat Ltd. and Luke, a constructed wetland system for wastewater effluent by Gdansk Water Utilities, Poland, and a constructed wetland system for stormwater treatment by Gdansk Water. The results obtained from the four MP removal pilots were very promising. The filter consisting of harvested and bundled common reed is cost-effective and locally adaptable. However, due the insufficient time available for maturation of the reed filter, its performance in MP removal remained uncertain. Novel snow melting and filtering technology developed by Clewat Ltd. solves the problem of dumping urban snow untreated into the sea in a sustainable way. In this project, the efficiency of the snow treatment unit in MP removal was optimized concerning the mesh size for the finer filter used. The constructed wetland systems piloted showed MP removal efficiencies up to 90% from urban stormwaters and wastewater treatment plant effluent. In addition to retention of MPs present in various urban waters, high removal rates were demonstrated for total suspended solids, nutrients and various pollutants. However, additional longer-time pilot experiments are needed to optimize the performance of the systems, especially for those based on vegetation and biofilm formation. Environmental impact and techno-economic feasibility assessments were also performed for the piloted technologies.
Keywords: microplastic; removal technology; pilot; common reed; constructed wetland; snow; stormwater; wastewater